Longitudinal Changes and Recovery in Heart Rate Variability of Young Healthy Subjects When Exposure to a Hypobaric Hypoxic Environment - Ma, Chenbin; Xu, Haoran; Yan, Muyang; Huang, Jie; Yan, Wei; Lan, Ke; Wang, Jing; Zhang, Zhengbo (Frontiers in Physiology, 2022)
Background: The autonomic nervous system (ANS) is crucial for acclimatization. Investigating the responses of acute exposure to a hypoxic environment may provide some knowledge of the cardiopulmonary system's adjustment mechanism. Objective: The present study investigates the longitudinal changes and recovery in heart rate variability (HRV) in a young healthy population when exposed to a simulated plateau environment. Methods: The study followed a strict experimental paradigm in which physiological signals were collected from 33 healthy college students (26±2 years, 171±7 cm, 64±11 kg) using a medical-grade wearable device. The subjects were asked to sit in normoxic (approximately 101 kPa) and hypoxic (4000 m above sea level, about 62 kPa) environments. The whole experimental process was divided into four stable resting measurement segments in chronological order to analyze the longitudinal changes of physical stress and recovery phases. Seventy-six time-domain, frequency-domain and non-linear indicators characterizing rhythm variability were analyzed in the four groups. Results: Compared to normobaric normoxia, participants in hypobaric hypoxia had significantly lower HRV time-domain metrics such as RMSSD, MeanNN, MedianNN (p < 0.01), substantially higher frequency domain metrics such as LF/HF ratio (p < 0.05), significantly lower Poincaré plot parameters such as SD1 /SD2 ratio and other Poincaré plot parameters are reduced considerably (p < 0.01), and RCMSE curves are reduced significantly (p < 0.01). Conclusion: The present study shows that elevated heart rates, sympathetic activation, and reduced overall complexity were observed in healthy subjects exposed to a hypobaric and hypoxic environment. Moreover, the results indicated that Multiscale Entropy analysis of RR interval series could characterize the degree of minor physiological changes. This novel index of heart rate variability can better explain changes in the human autonomic nervous system.